Performance of high-temperature enhanced biological phosphorus removal process and microbial study of its polyphosphate accumulating organisms and glycogen accumulating organisms / Ong Ying Hui - Ong, Ying Hui (2015)
Enhanced biological phosphorus removal (EBPR) process is commonly applied for the removal of phosphorus (P) from wastewater. Realizing the rapid urbanization and population growth around the world, nutrient pollution problems has gained global concerns. The increasing array of Malaysia’s regulatory requirements on sewage treatment plants (STPs) is part of the abatement strategies on nutrient pollution issue. Reliably meeting low effluent limits can be difficult when EBPR process operated at temperature higher than 25oC. Thus, there is an urgent need to evaluate the applicability and compliance accountability of EBPR process for STPs in tropical climates with relatively high temperatures around 25oC - 32oC. In this study, the EBPR performance at the temperature range of 24oC - 32oC and its microbiological aspects, the population abundance and dynamic of PAOs and GAOs as well as the fine scale population of Candidatus “Accumulibacter phosphatis” (hereafter named Accumulibacter) were investigated. Two sequencing batch reactors (SBRs) were operated parallel for high-temperature EBPR processes. SBR-1 was continuously operated at 28oC while SBR-2 first at 24oC and subsequently at 32oC. Both SBRs exhibited high P removal efficiencies at all three temperatures and produced effluent with P concentration less than 1.0 mg/L. Using fluorescent in situ hybridization (FISH), potential PAOs and GAOs were screened. It was discovered that Accumulibacter and Candidatus “Competibacter phosphatis” (hereafter named Competibacter) emerged as major PAOs and GAOs. Further, the population dynamics of Accumulibacter-PAOs and the abundance of Competibacter-GAOs were monitored by real-time quantitative polymerase chain reaction (qPCR) and FISH respectively. 16S rRNA-based qPCR revealed Accumulibacter-PAOs comprised 64% of the total bacterial population at 24oC, 43% at 28oC and 19% at 32oC. FISH revealed the abundance of Competibacter-GAOs at both 24oC and 28oC was rather low (< 10%), while it accounted for 40% of total bacterial population at 32oC. Obviously, smaller population of Accumulibacter-PAOs and larger population of Competibacter-GAOs did not reduce the EBPR activity in 32oC. Following, polyphosphate kinase 1 gene (ppk1) based clone library was constructed to unveil the fine-scale population of Accumulibacter-PAOs. Clade IIF was discovered as the only Accumulibacter clade present. More quantitatively, ppk1 based qPCR was employed to study the dynamic patterns of clade IIF in the EBPR processes. The specific primers set for qPCR assay exclusively target on clade IIF was developed. Primers Acc-ppk1-355f and Acc-ppk1-600r were successfully designed in this study. The average abundance of Accumulibacter clade IIF assayed by qPCR was 54% at 24C, 40% at 28C, and 12% at 32C. Despite lower abundance of clade IIF, the EBPR sludge of 32oC possessed similar P content (7- 8%) to the other two temperatures. Good EBPR activity at 32oC could be associated with the greater P accumulation capability in Accumulibacter clade IIF. This research demonstrated good EBPR activity could be achieved at high temperatures. This is also the first report on the distribution of Accumulibacter clades in high-temperature EBPR process. Larger population in Competibacter-GAOs than Accumulibacter-PAOs did not deteriorate good EBPR performance. Accumulibacter clade IIF was robust and could tolerate high temperatures. This suggests the presence of particular Accumulibacter clade(s) and its ecophysiological role drive the EBPR activity. Also, it reflects the Accumulibacter-PAOs may have variable sensitivity to temperature among the lineages.